First Report of the Gastropod-Killing Nematode, Phasmarhabditis californica, in Washington State, U.S.A - Mc Donnell Rory J.; K. Howe Dana; R. Denver Dee (Journal of Nematology, 2023)
Phasmarhabditis californica, a commercially available biological control agent in England, Scotland, and Wales (Nemaslug 2.0 ®), was discovered for the first time in Washington State during 2022. Nematodes were recovered from the invasive gastropods Arion hortensis, Deroceras reticulatum, and Oxychilus sp. in garden centers in both Vancouver and Spokane. The 18S ribosomal RNA gene was used to identify the nematodes. This discovery builds upon previous reports of P. californica in California and Oregon and suggests that the species is widespread throughout the west coast of the U.S. Future research directions with P. californica are proposed.